Value Orientations of the Academic Youth - Purvaneckienė, Giedrė (Acta Paedagogica Vilnensia, 1993)
This article is based on a paper presented at the Seventh Symposium on Arts and Sciences of the Lithuanians of the World. The analysis of the value orientations of academic youth is based on the surveys performed in 1989 and 1990 at Vilnius University Laboratory of Sociology. The 1989 survey of the senior pupils and students revealed that Lithuanian youth considers communication within the family as one of the most important of activities. Although significant social changes occurred, in 1990 youth value orientations survey also revealed that the importance of the family, this primary and most secure unit, is far from diminished. Summarizing the research data, the attitudes of Lithuanian youth towards the family may be called traditional and patriarchal. The research methodology was consistent with the methodology of the Western European youth value survey, making it possible to compare the results. Basically the evaluation by Lithuanian youth of various family factors, such as mutual respect and understanding, fidelity, children, good sexual relationships, tolerance, sufficient income, the same religion, etc., are little different from those of the Western European youth. However, Western youth assigns more importance to tolerance and sexual relations, Lithuanian youth to children and good living conditions. Much higher difference of assessments is observed when it comes to the relationship between parents and children, the congruence of views.
Keywords: university students; value orientations; attitudes; family